Knowledge, perceived risk and the associated preventive behaviours amidst COVID-19 pandemic among undergraduate dental students in Malaysia - Ismail, Nur Hanisah; Abu Kassim, Nur Yasrin Maisarah; Ismail, Azlini; Lestari, Widya; Ismail, Ahmad Faisal; Sukotjo, Cortino (2022)
Introduction: Coronavirus disease 19 (COVID-19) is a dreadful disease that affected many sectors including dental practice in Malaysia. However, studies on dental students' knowledge, perception, and behaviours with regards to COVID-19 are very limited. Thus, this study aims to determine the knowledge status, perceived risk, and preventive behaviours of dental students in Malaysia on COVID-19. Materials and methods: A cross-sectional study was conducted among undergraduate dental students from 13 dental schools across Malaysia using online questionnaires. Results: From 355 respondents, 93.5% obtained a high score of knowledge on COVID-19. Female respondents scored higher than males in perceived risks and preventive behaviours. Chinese respondents scored highest in knowledge, while Malay respondents had the highest perceived risk score. The mean preventive behaviours score did not vary across ethnicity. On-campus students scored higher in knowledge and perceived risk whereas off-campus students practiced more preventive behaviours. Clinical students’ knowledge score was higher than preclinical students. Final year students scored higher in knowledge and perceived risk compared to their juniors. Conclusion: Majority of dental students have good knowledge and high perceived risk of COVID-19, and they practiced most of the preventive behaviours. However, the latest information on this disease should be incorporated into dental schools' curriculums and updated periodically.